2021
DOI: 10.3389/frobt.2021.677542
|View full text |Cite
|
Sign up to set email alerts
|

The i-Walk Lightweight Assistive Rollator: First Evaluation Study

Abstract: Robots can play a significant role as assistive devices for people with movement impairment and mild cognitive deficit. In this paper we present an overview of the lightweight i-Walk intelligent robotic rollator, which offers cognitive and mobility assistance to the elderly and to people with light to moderate mobility impairment. The utility, usability, safety and technical performance of the device is investigated through a clinical study, which took place at a rehabilitation center in Greece involving real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The research project reported here included four studies, which together provide a comprehensive evaluation of the prototype frame design. The approach taken is in line with recent research that likewise used objective and subjective measures for evaluation of an intelligent walker [25], however, the prototype frame evaluated here is a passive device and its novel features do not require power. Quantitative stability analysis of healthy older adults using a standard walking frame and the prototype frame demonstrated that the prototype frame design increases stability during performance of complex everyday tasks: the stability margin improved by ~ 10-40 mm in some cases indicating that the user-device system was further from the point of "tipping over" as compared to the standard frame.…”
Section: Discussionmentioning
confidence: 77%
“…The research project reported here included four studies, which together provide a comprehensive evaluation of the prototype frame design. The approach taken is in line with recent research that likewise used objective and subjective measures for evaluation of an intelligent walker [25], however, the prototype frame evaluated here is a passive device and its novel features do not require power. Quantitative stability analysis of healthy older adults using a standard walking frame and the prototype frame demonstrated that the prototype frame design increases stability during performance of complex everyday tasks: the stability margin improved by ~ 10-40 mm in some cases indicating that the user-device system was further from the point of "tipping over" as compared to the standard frame.…”
Section: Discussionmentioning
confidence: 77%
“…The intelligent robotic rollator, e.g., i-Walk, is an integrated set of sensing, navigation, and user-robot interaction modules, which are designed in such a way as to enable the real-time operation to support the envisioned user-assisted functions [19]. They are suitable for providing cognitive and walking assistance to people with mild to moderate motor impairments (e.g., the elderly), and they can combine user-adaptive motion control, navigation in dynamic environments, and cognitive assistance.…”
Section: Intelligent Robotic Rollator Integrally Enhances Physical An...mentioning
confidence: 99%
“…Indeed, all reviewed approaches rely on on-board sensors, such as force sensors [8], [35], [47], [59], force and torque sensors [24] or load cells [50]. In addition, a platform contains a voice interaction system, the user uses speech to express their intention [40].…”
Section: A User Interfacesmentioning
confidence: 99%
“…Personalized Guide or improve users' gait using visual [25], [29], [57] or acoustic feedback [34]. Guidance the users to place they want to go using audio cues [40]. Guidance using resistive or assistive forces [47].…”
Section: Autonomoushumanmentioning
confidence: 99%
See 1 more Smart Citation